Survey of Postoperative Pain in Photorefractive Keratectomy Using Topical versus Oral Nonsteroidal Anti-Inflammatory Drugs - Ripa M (Dove Medical Press, 2020)
Madeline Ripa,1 Brent Betts,1 Shagun Dhaliwal,1 Kaidi Wang,1 Severin Pouly,1 Danli Chen,2 Mark Mifflin1 1Department of Ophthalmology and Visual Sciences, John A. Moran Eye Center, University of Utah, Salt Lake City, UT, USA; 2Division of Epidemiology, University of Utah, Salt Lake City, UT, USACorrespondence: Mark Mifflin Email mark.mifflin@hsc.utah.eduPurpose: To evaluate and compare postoperative pain following photorefractive keratectomy (PRK) in patients using a preventive regimen of oral versus topical nonsteroidal anti-inflammatory drugs (NSAIDs).Patients and Methods: A prospective, randomized, longitudinal survey of postoperative PRK pain was performed on 157 subjects in a tertiary academic medical center setting. Patients were randomized to either topical ketorolac 0.4% every 12 hours or oral naproxen sodium 220 mg every 12 hours for 72 hours following PRK, beginning at the time of surgery. The primary outcome measure was the daily peak pain score from the validated numerical rating scale (NRS) for five days after surgery.Results: The peak pain scores were significantly higher in the oral NSAID group (mean 5.82, SD 1.94) compared to the topical NSAID group (mean 4.2, SD 2.19) (p< 0.0001) after PRK. When comparing each postoperative day after PRK, the pain scores from 24 to 48 hours (day 2) were significantly higher in the oral NSAID group (mean 5.17, SD 2.25) as compared to the topical NSAID group (mean 3.21, SD 2.09) (p< 0.0001). Pain scores 24– 72 hours after surgery (days 2 and 3) were higher than pain scores on days 1, 4, and 5 for both groups.Conclusion: Twice daily oral naproxen sodium 220 mg is inferior to twice daily topical ketorolac 0.4% in the treatment of early postoperative pain after PRK. This study also identified a consistent trend in which pain scores were highest 24– 72 hours after the procedure. This additional observation may be useful in understanding, preventing, and treating post-PRK pain.Keywords: pain, refractive surgery, photorefractive keratectomy, nonsteroidal anti-inflammatory drugs, naproxen, ketorolac